Employing Reading Racetrack and Flashcards to Enhance Sight Words Recognition Among Students with Learning Disability - Norhayati Othman; Mohd Mokhtar Tahar (Department of Special Education, 2017)
Effective sight words instruction will improve a student’s overall reading abilities. This study involved a replication of an instructional reading strategy in measuring the effects of pairing reading racetracks with flashcards in enhancing sight words recognition of student with learning disability. Two six-year old students have been selected by their classroom teacher to participate based on their reading performance. Data were collected based on the number of corrects and errors of selected sight words presented to them. The results indicated that each student improved their performance on sight words reading when racetrack and flashcards were used. The efficacy of employing reading racetracks and flashcards at the classroom level was discussed.